Silicone insulation tilt angle impact on its performance under 1000 h of salt fog aging and AC voltage - SLIMANI, Samia (Biopolymer Applications Journal, 2026)
<audio class="audio-for-speech"></audio> Translator <audio class="audio-for-speech"></audio> Translator The investigation focusses on the impact of the inclination angle with respect to the horizontal of hydrophobic elastomer silicone insulation on its performance during aging under salt fog and high AC voltage. The objective of this study is to quantify the leakage current along the surface of silicone insulation as a function of its inclination angle and duration of exposure to salt fog over 1000 hours ageing period. Upon completion of the ageing process, the silicone elastomer samples were characterized through surface roughness measurements, visual inspection of surface morphology, and evaluation of their hydrophobicity. The results indicated that no burn marks or surface erosion was observed on the insulation after exposure to salt fog. Furthermore, the hydrophobic properties of silicone insulation were effectively retained over time under salt fog conditions, particularly at high inclinations. These findings suggest that increasing the tilt angle contributes to improving insulation performance during 1000 h of salt fog exposure